To analyze the functional outcome of proximal tibial fractures treated with minimally invasive percutaneous plate osteosynthesis technique - Arumugam, Sivakumar; Arumugam, Venkateshwara; Raviraman, V. (International Journal of Research in Orthopaedics, 2017)
Background: Tibial plateau fractures constitute about 1% of all fractures and complex bicondylar fractures constitute 30% of all Tibial plateau fractures. Minimally Invasive Percutaneous Plate Osteosynthesis [MIPPO] is a method of biological fixation in which a plate is percutaneously inserted and fixed at a distance proximally and distally from the fracture site. By minimal exposure, this helps in the preservation of the essential fracture hematoma, minimal soft tissue dissection, avoidance of periosteal stripping and providing an adequate fixation. The objective of the study was to analyze the functional outcome of proximal Tibial fractures treated with MIPPO technique. The method of fixation shall be evaluated for the time period required for the patients to return to active work following surgery. Methods: In our study, all 18 patients with proximal Tibial fractures underwent definitive fixation by MIPPO technique. All our cases underwent initial stabilization as per the ATLS guidelines. Patients with closed Tibial plateau fractures associated with a tense haemarthrosis underwent aspiration of the joint under aseptic precautions. The limb was immobilized either in an above knee slab or through skeletal traction using a distal Tibial or calcaneal pin traction on a Bohler Braun splint until definitive fixation was carried out. In cases complicated with excessive swelling and blistering, definitive fixation was delayed until the swelling/ blistering subsided. Results: The post-operative results were designated as excellent, good, fair and poor according to pain, walking capacity, the range of motion and stability of the knee using Rasmussen’s grading system. In our study, the average functional knee score was 22.89. Rasmussen’s score does not consider articular congruity while assessing the functional outcome of the knee. Conclusions: MIPPO technique gives good to excellent results even in high energy Tibial condyle fractures [72.22% cases in our study]. Our patients were able to achieve a good functional range of movement, averaging 120 degrees. [Krettek et al – 124 degrees]. Those who were treated with early fixation and early mobilization were found to have a better functional outcome irrespective of the fracture type. No secondary bone grafting was required.